e-Learning research: emerging issues? - Helen Beetham (Association for Learning Technology, 2005)
e-Learning research is an expanding and diversifying field of study. Specialist research units and departments proliferate. Postgraduate courses recruit well in the UK and overseas, with an increasing focus on critical and research-based aspects of the field, as well as the more obvious professional development requirements. Following this year's launch of a National e-Learning Research Centre, it is timely to debate what the field of study should be prioritising for the future. This discussion piece suggests that the focus should fall on questions that are both clear and tractable for researchers, and likely to have a real impact on learners and practitioners. Suggested questions are based on early findings from a series of JISC-funded projects on e-learning and pedagogy.